Pengaruh Aplikasi Refrigeran Hidrokarbon Terhadap Performansi Mobile Air Conditioning - Puji Saksono (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2014)
AbstractRefrigeration system this day has been developed fastly in advance technology manner. In general this system is developed to preserve food and to refresh the air condition. One of the usage of this system for Mobile Air Conditioning (MAC). The Global warming issues then become the limitation of the usage of refrigerant system of R-134a. As the replacement, retrofit process is conducted to change to refrigerant Hydrocarbon (HC) type. This research has objective to find the performance of those two types refrigerants. The test was conducted by using testing tool from MAC system that had been modified with control addition equipments. The result of the test toward testing tool of Mobile Air Conditioning, the mass number of refrigerant in full level condition of HC-134 is less than R-134a. The mass of R-134a was 420 gram while HC-134 was 240 gram. Beside the usage of refrigerant is lesser than normal condition, the aplication of HC-134 can give coeffcient of performance (COP) higher value than R-134a. Keywords: refrigerant type, refrigeratIon effect, compression work, COP AbstrakSystem pendingin pada saat ini telah banyak berkembang pesat seiring dengan kemajuan teknologi. Pada umumnya sistem ini digunakan untuk mengawetkan makanan dan penyegaran udara. Salah satu pemanfaatannya yaitu pada Mobile Air Conditioning (MAC). Isu pemanasan global di bumi menjadi bagian pembatasan pemakaian refrigeran R-134a, dan sebagai gantinya dilakukan retrofit ke jenis refrigeran Hydrocarbon (HC). Penelitian ini bertujuan untuk mengetahui performansi dari kedua jenis refrigeran tersebut. Pengujian dilakukan dengan menggunakan alat uji dari sistem MAC yang telah dimodifikasi dengan peralatan kontrol. Hasil pengujian pada alat uji Mobile Air Conditioning, jumlah massa refrigeran pada isian penuh HC-134 lebih sedikit dibandingkan dengan R-134a. Untuk R-134a sebesar 420 gram, sedangkan HC-134 sebesar 240 gram. Disamping pemakaian refrigeran yang lebih sedikit, aplikasi HC-134 juga memberikan nilai COP (coeffcient of performance) yang lebih tinggi dibanding dengan R-134a. Kata kunci: Jenis refrigerasi, efek refrigerasi, kerja kompresi, COP.